Disarming abusers: domestic violence protective order (DVPO) firearm restriction processes and dispositions - Kafka, Julie M. (Criminology & public policy, 2022)
Research summary We investigated the degree to which legislatively mandated firearm restrictions for domestic violence protective orders (DVPOs) have been implemented in North Carolina. We used a representative sample of n = 406 DVPO hearings (2016-17) and found that defendant access to firearms was seldom discussed (23.81%). Among granted orders (n = 303), 69.5% prohibited defendant firearm possession (n = 238) but only 38.61% ordered firearm surrender (n = 143). There were higher odds of restrictions when the defendant had threatened to kill the plaintiff (OR for prohibited possession: 2.25, CI: 1.02, 4.97; OR for firearm surrender: 1.93, CI: 1.09, 3.40); no other lethality indicators were significant. Judges verbally announced firearm restrictions only in one out of three cases (30.87% of DVPOs granted with prohibited possession; 33.02% of firearm surrender cases). Policy implications Protocol to assess firearm access, implement firearm restrictions, and communicate these provisions to litigants must be more clearly and consistently applied in the courtroom.